(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Lorentz transformation relations of special relativity are generally derived for light like intervals in almost all texts. The procedure assumes invariance of spherical wave front equation in all inertial frames. This paper deals with the derivation of the transformation relations of event coordinates together with Doppler formula from a single treatment by constructing identical length and time standard under identical conditions in compared frames. To meet this end critical review of the postulates of Special Relativity in the perspective of equivalence of length, time and mass standard followed by the meaning of phase of clock in any inertial frame is presented. It has been shown that special relativity is in reality a supreme creation of human mind where identical length and time standards being independent of the perspective are not naturally given but had been constructed under identical experimental condition in a scientific way so that observations from different frames can be compared using same system of units.